1996
DOI: 10.1172/jci118615
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia inhibitory factor (LIF) stimulates proopiomelanocortin (POMC) expression in a corticotroph cell line. Role of STAT pathway.

Abstract: We recently described the expression of leukemia inhibitory factor (LIF) in human fetal and murine corticotrophs. LIF and the related cytokine oncostatin M induced basal, and corticotropin-releasing hormone (CRH) induced proopiomelanocortin (POMC) mRNA and ACTH secretion in AtT20 cells. LIF signaling and regulation of POMC gene transcription were therefore tested. Dexamethasone inhibited both basal-and LIF-induced ACTH secretion ( P Ͻ 0.05) and LIF induction of ACTH was also attenuated by immunoneutralization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(110 citation statements)
references
References 40 publications
4
104
0
2
Order By: Relevance
“…Here, we found that CRH stimulated the rat POMC promoter K480/C63 construct, while pCPT-cAMP stimulated the rat POMC promoter K480/C63 construct to a large degree. This result coincides with those of previous reports (Jeannotte et al 1987, Ray et al 1996, Kovalovsky et al 2002, Mynard et al 2004. The low promoter activation of CRH treatment might be due to low cAMP generation, because there are some reports that described low and transient cAMP accumulation on CRH stimulation in AtT-20 cells (Litvin et al 1984, Nikodemova et al 2003.…”
Section: Discussionsupporting
confidence: 94%
“…Here, we found that CRH stimulated the rat POMC promoter K480/C63 construct, while pCPT-cAMP stimulated the rat POMC promoter K480/C63 construct to a large degree. This result coincides with those of previous reports (Jeannotte et al 1987, Ray et al 1996, Kovalovsky et al 2002, Mynard et al 2004. The low promoter activation of CRH treatment might be due to low cAMP generation, because there are some reports that described low and transient cAMP accumulation on CRH stimulation in AtT-20 cells (Litvin et al 1984, Nikodemova et al 2003.…”
Section: Discussionsupporting
confidence: 94%
“…Model of interaction and negative autoregulatory feedback of SOCS-3 protein on POMC and SOCS-3 gene expression. The LIF-induced signaling cascade in the corticotroph cell envolves tyrosine phosphorylation of gp130, STAT-3, and STAT-1 (15,23,26,27). LIF induces gene expression of POMC (28) and SOCS-3 in the corticotroph cell in a STAT-3 dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments using human fetal pituitary cells (23) and the corticotroph cell line AtT-20 (24,25) showed a profound synergistic action of LIF and corticotropin-releasing hormone on POMC gene expression and ACTH secretion. The LIF-induced signaling cascade in the corticotroph cell involves phosphorylation of gp130, STAT-3, and STAT-1 (15,23,26,27), and LIF-induced POMC expression and ACTH secretion is STAT-3 dependent (28). SOCS-3 gene expression is rapidly induced by LIF in the pituitary in vivo and in corticotroph AtT-20 cells in vitro (15).…”
mentioning
confidence: 99%
“…The membrane was washed in Trisbuffered saline with 0·1% Tween 20, and the secondary antibody, anti mouse-hrp (Amersham) used at 1:2000 dilution in blocking buffer. Detection was by enhanced chemiluminescence (ECL) as previously described (Ray et al 1996b).…”
Section: Immunoblottingmentioning
confidence: 99%